Cp*RhIII‐Catalyzed Sterically Controlled C(sp3)−H Selective Mono‐ and Diarylation of 8‐Methylquinolines with Organoborons. Issue 19 (11th March 2020) - Kumar, Rakesh; Parmar, Diksha; Gupta, Shiv Shankar; Chandra, Devesh; Dhiman, Ankit Kumar; Sharma, Upendra
Abstract: Herein, the Rh III ‐catalyzed selective monoarylation and diarylation (symmetrical and unsymmetrical) of 8‐methylquinolines with organoboron reagents are disclosed. The selective monoarylation of primary C(sp 3 )−H bonds is achieved by using 7‐substituted 8‐methylquinolines or by changing the quantity of the aryl boronic acids. The method is also applicable for the arylation of 2‐ethylpyridines, and the heteroarylation with thiophene‐2‐ylboronic acids. Symmetrical and unsymmetrical diarylation of 8‐methylquinolines have been carried out in one‐pot and sequential manner, respectively. Late‐stage monoarylation of oxime derivatives and gram‐scale synthesis of monoarylated products has also been carried out. A mechanistic study revealed that the current reaction is first order with respect to both reactants and a five‐membered rhodacycle intermediate may be involved in the catalytic cycle. Abstract : Arylation : Monoarylation of the C(sp 3 )−H bonds of 8‐methylquinolines is disclosed along with symmetrical and unsymmetrical diarylation of 8‐methylquinolines in one‐pot and sequential manner, respectively. The order of the reaction with respect to each reactant is first order.